KEHIDUPAN LESBIAN PADA NOVEL KEMBANG KERTAS IJINKAN AKU MENJADI LESBIAN KARYA ENI MARTINI (KAJIAN SOSIOLOGIS) - Sarleoki Nancy Umkeketony (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to describe lesbian life as depicted in the novel Kembang Kertas: Ijinkan Aku Menjadi Lesbian by Eni Martini using a sociological approach. The research employs a descriptive qualitative method, with the novel text serving as the primary data source. Data were collected through intensive reading and systematic note-taking of excerpts relevant to the research focus. Data analysis was conducted by relating narrative elements to the social realities of Indonesian society. The findings indicate that lesbian life in the novel is portrayed through the existential experiences of the main character, who undergoes profound inner conflict in the search for identity while simultaneously facing strong social rejection, negative stigma, and psychological pressure from family and the surrounding environment. The novel functions as a sharp form of social criticism toward discriminatory attitudes within society. This study contributes significantly to the development of literary sociology, particularly by enriching insights into the representation of sexual minority groups in Indonesian literature and by reinforcing the role of literature as a social document that records cultural value conflicts within society.